Analytical review of the framework of the reuse of treated wastewater for agriculture under Algeria’s 2030 water resources strategy - سردوك, فاتح; عابي, خليدة; محسن, زوبيدة (University of Eloued جامعة الوادي, 2019)
ABSTRACT Wastewater is produced by human activity and has a direct impact on the natural environment in which it is discharged, whether treated or not. Responsible management of increasing volumes of wastewater represents a real health and environmental challenge for all involved actors (local authorities, operators, etc.), worldwide. Effective treatment solutions exist, including the possible reuse of treated wastewater. Water is a prerequisite for economic growth and prosperity. as well as the basis of ecosystems, vital for human health and well-being, for this, it has been strongly presented at the heart of the 2030 Agenda for Sustainable Development. through UN-Water integrated monitoring for achieving the Sustainable Development Goals (SDGs) 6. where cited that the availability and sustainable management of water and sanitation are closely linked to all other sustainable development goals. In the light of this global view, theaim of this paper is to give an analytical review the status of wastewater treatment in Algeria as a main unconventional water resources for irrigating agricultural crops, as well as to reviewing the prospects for investment in the reuse of treated wastewater in irrigation under the Algeria’s water resources strategy by2030.
الملتقى الدولي السابع حول اقتصاديات الإنتاج الزراعي في ظل خصوصيات المناطق الزراعية في الجزائر والدول العربية 30- 31 أكتوبر 2019 كلية العلوم الاقتصادية والتجارية وعلوم التسيير جامعة الشهيد حمه لخضر الوادي